Groundswell Africa A Deep Dive Into Internal Climate Migration in Uganda - Rigaud, Kanta Kumari (Other papers, 2021)
Uganda is a diverse and verdant country. From the tall volcanic mountains along the eastern and western borders to the densely forested wetlands of the Albert Nile River and the rainforests in the center of the country, it encompasses many different ecosystems. Kampala, the capital city, is built around seven hills not far from the shores of Lake Victoria. These varying landscapes provide Ugandans with ample resources to capitalize on tourism and cultivate crops, including Ugandan coffee, which has become a favorite of coffee drinkers around the world. These rich and beautiful landscapes, however, are under threat from climate change, which could have disastrous effects for Ugandans. This report shows that by 2050, as many as 12 million people, or 11 percent of the population could move within Uganda because of slow onset climate factors, without concrete climate and development action.